Estimating Willingness-to-Pay Values to Improve the PDAM Clean Water in Surabaya - Hidayati, Nur Aini (International Journal of Psychosocial Rehabilitation, 2020)
Clean water plays an important role in every activity of mankind—in household, commercial, industrial, as well as public and social sectors. As the second biggest city after Jakarta, Surabaya faces a fundamental issue of basic needs, which is the poor quality of clean water for domestic use. Polluted water due to contaminants has been a daily issue in Surabaya. Therefore, the aim of this research is to estimate the economic value of clean water accrued to households in Surabaya city, the capital of East Java Province in Indonesia. The economic valuation was carried out by determining households’ willingness to pay for improved water quality and reliability of supply through the Contingent Valuation technique. The valuation is limited to urban households in this context is PDAM customer. This paper results the aggregate value of water quality and reliability improvements have been substantial such that it warrants PDAM to improve the quality of pertinent services. However, such provision will be contingent on a further cost-benefit valuation based on its affordability of supply relative to demand.